Demographic Factors Influence on the Tendency to Become Entrepreneur: Estimating the Antecedents and Consequences of Entrepreneurial Tendency - Polas, Mohammad Rashed Hasan; Bhattacharjee, Amitab; Raju, Valliappan; Hossain, Mohammad Imtiaz (International Journal of Management and Sustainability, 2019)
The essence of this study deals with identifying the major demographic factors for the tendency to become an entrepreneur. Our survey data from 132 randomly selected respondents were used to investigating the factors for the tendency to become an entrepreneur. In this study, a quantitative method was used to improve research strength. This study identified some major factors which increase an individual’s entrepreneurial tendency. The study found a significant relationship between educational degree specialization, nationality, gender, entrepreneur parent, child position, marital status, age towards the tendency to become an entrepreneur. Moreover, the study further didn’t find any relationship between performance (CGPA), religion and abroad experience towards the tendency to become an entrepreneur than earlier findings. Moreover, the entrepreneur is the combination of risk and willingness to find success but it’s not easy to be like that because of both effects of internal and external business environments and therefore this study is conducted to identify core factors, which may influence on the willingness of an individual for being an entrepreneur. It is truly noticed the business-oriented scope for female compared to male in the same region that supports the other major factor called nationality. However, this study is conducted over postgraduate students studying in Malaysia that may focus a limitation but its overall results will fairly demonstration tendency to become an entrepreneur based on the international business environment perspective.